Myocardial ultrastructural changes during extracorporeal circulation wtih anoxic cardiac arrest and its prevention by coronary perfusion. Experimental study. Issue 4 (August 1975) - Balibrea, J L; Bullon, A; de la Fuente, A; de la Alarcon, A; Fariñas, J; Collantes, P; Gil, M; Gombau, M; Morales, R; Sanchez, F
Abstract : This experimental work has been carried out with the aim of studying the ultrastructural myocardial changes caused by prolonged anoxic cardiac arrest during cardiopulmonary bypass, and their prevention by means of two different techniques of coronary perfusion–systemic-pressure continuous and low-pressure intermittent perfusion. After 30 minutes of cardiac anoxia, the ultrastructural changes of the myocardial cell were reverted to normal by coronary perfusion; when anoxic cardiac arrest was prolonged up to 60 minutes there was severe myocardial damage, with marked mitochondrial changes and dehiscence of intercalated discs, which persisted in spite of restoring coronary flow. These morphological data were in accordance with the fact that no dog which underwent anoxic cardiac arrest for 60 minutes recovered. Both intermittent and continuous coronary perfusion were effective in preventing anoxic damage; cardiac muscle cells were better preserved by low-pressure intermittent perfusion than by systemic-pressure continuous perfusion, which caused intracellular and intramitochondrial oedema.